대중문화 텍스트에 관한 SNS 비평 담론 연구 - 아이유 를 둘러싼 미학적 해석의 차이를 중심으로 - 우지혜; 백선기; Woo, Jihye; Baek, Seon Gi (한국콘텐츠학회 논문지, 17(1), 2017)
Criticism is related with recognition activity which is interpreting and evaluating the text based on the particular criteria. It reflects the awareness system of a particular time-period in that it is a work of social meanings beyond individual impressions. However, the standards of criticism have changed, like the awareness system has changed as economy, culture or technology has evolved. The emergence of SNS has influenced the field of popular culture. It improves the role and participation of the public in criticism. Moreover, it breaks the previous paradigm of production and consumption in cultural industry. These changes bring not only the positive ones, such as improvement of diversity and freedom of criticism, but also the negative one, confusion of values due to the absence of criteria. This study mainly concerned debates and discourses of SNS on , a new song of IU, and focused on changes of aesthetic evaluations of culture performer, producer and audience. Especially, the authors tried to find out how such new technology has changed the criticism, and how it has influenced on our aesthetic consciousness. 비평은 텍스트의 의미를 해석하고 평가하는 일종의 인식 행위다. 이는 개인의 감상을 넘어 작품에 대한 사회적 의미를 부여하는 작업이라는 점에서 한 시대의 인식 체계를 반영한다. 그런데 인식 체계가 고정된 것이 아니라 경제 문화 기술의 발전에 따라 변화 하듯이, 비평의 기준 또한 사회의 변화에 의해 달라진다. 오늘날 SNS의 등장은 대중문화 비평에 있어 대중의 역할과 참여를 비약적으로 증대시키고, 대중문화 생산-소비의 패러다임을 변화시키는 등 기존의 비평과 다른 환경을 제공하였다. 이는 비평의 다양성 및 자유 확대 등 긍정적 변화들을 가져왔으나, 한편으로는 무비판적인 비난 혹은 옹호, 비평의 기준 부재로 인한 가치 혼란이라는 부정적 결과 또한 초래했다. 이처럼 새로운 기술의 도입은 기존의 비평 행위와 그 이면의 인식 틀에 변화를 가져왔다. 본 연구는 아이유의 관련 논쟁에 대해 SNS을 통해 전개되는 담론에서 문화 행위자, 생산자 및 수용자의 비평 행위가 어떻게 전개되며 그로 인한 파장이 어떠한 가에 대해 분석했다. 궁극적으로는 SNS라는 새로운 매체 기술을 통해 비평의 행위가 기존과 어떻게 달라졌으며, 나아가 우리의 인식 체계, 특히 미의식에 어떠한 영향을 미쳤는지를 고찰했다.